Emancipatory Pedagogy Teaching of Gender in an Elementary Teacher Education Programme - Bassi, Tripti (JOURNAL OF INDIAN EDUCATION, 2021)
This article focuses on the transaction of Gender and Schooling course to final year graduate students of B.El.Ed programme of University of Delhi in achieving knowledge goals—self-awareness, actualisation and change agency by these student-teachers. NCF 2005 and National Education Policy 2020 emphasise the need to address gender-related issues in our schools and in the society at large. Gender relations are a lens to study inequity between women and men in the society. These are essentially relations of power in which women have far less substantive power in relation to men. These relations manifest in explicit and implicit ways. The student-teachers study the Gender and Schooling course in their final year for theoretical understanding as well as critical examination and application during their school internship in the same year, operationalising what NCFTE calls the linking of book-view to fieldview. The gender course in the B.El.Ed. programme acts as a discursive field of knowledge, empowerment and action.